Nutrient Composition Comparison between the Low Saturated Fat Swank Diet for Multiple Sclerosis and Healthy U.S.-Style Eating Pattern - Chenard, Catherine A. (Nutrients, 2019)
Multiple sclerosis (MS) is an incurable degenerative disease that attacks the central nervous system. Roy Swank proposed a low saturated fat diet to treat MS around 1950 and showed delayed disease progression in his patients. However, there is insufficient evidence to recommend this diet for MS and default dietary recommendations are the Dietary Guidelines for Americans (DGA). This study assessed the nutritional adequacy of seven-day menus developed by Swank and their compliance with the DGA; menus were modeled for comparison with the DGA Healthy US-Style Eating Pattern (HEP) for males and females 31–50 years. Swank recommended dietary supplements corrected menu shortfalls in vitamins D, E, calcium, folate and iron but not dietary fiber, potassium and choline. Healthy Eating Index-2015 score for Swank menus (93.2/100) indicated good compliance with the DGA. Nutritional adequacy of the Swank modeled diet was similar to HEP for 17 vitamins and minerals (Mean Adequacy Ratios ≥94%) with similar shortfall nutrients except magnesium (HEP males) and dietary fiber (Swank males). Alternate Healthy Eating Index-2010 scores for Swank male (90/110) and female (88/110) model diets were similar to HEP. Swank menus have similar nutritional adequacy as HEP. Inclusion of foods high in dietary fiber, potassium and choline may be advised as well as selection of foods to reduce sodium below the Tolerable Upper Intake Level.